Phosphorus retention and availability in three contrasting soils amended with rice husk and corn cob biochar at varying pyrolysis temperatures - Eduah, J.O.; Nartey, E.K.; Abekoe, M.K.; Breuning-Madsen, H.; Andersen, M.N. (Geoderma, 2019)
The reactive nature of phosphorus (P) leads to the formation of insoluble Fe, Al and Ca phosphates in highly weathered tropical soils, thus reducing P availability for plant uptake. Biochar with its heterogeneous surface properties as influenced by feedstock and pyrolysis temperature can affect P retention and availability in tropical soils. In the present study, incubation studies were conducted for 90 days to investigate the effect of corn cob and rice husk biochar on P sorption and desorption in two acid (Typic Plinthustult-A & Plinthic Acrudox-B) and one neutral soil (Quartzipsamment-C). The biochars were pyrolyzed at varying temperatures (300 °C, 450 °C and 650 °C) and applied at a rate of 1% (w/w) to the soils. Phosphorus sorption data were fitted to Langmuir and Freundlich models. Phosphorus desorption was done on the residual samples that received initial P concentrations of 21.5 mg L−1, 43.0 mg L−1 and 86.0 mg L−1 solution using 10 mM KCl. The P sorption capacity of the two acid soils i.e. A (395 mg kg−1) and B (296 mg kg−1) were more than two fold that of the neutral soil (C) (105 mg kg−1). Addition of the biochar types to soil A raised the equilibrium P concentration in solution at decreasing pyrolysis temperature. Similar trend was observed in soil B with the exception of corn cob and rice husk biochar at 650 °C which increased the soil's (B) P sorption capacity. In soil C, both biochar types increased P sorption capacity with increasing pyrolysis temperatures. Phosphorus desorbability increased with increasing initial P concentrations in the three soils. Generally, P desorbability increased in the acid soils but decreased in the neutral soil upon biochar amendment. Decreases in P adsorption and consequently increases in P desorption were more pronounced when the 300 °C biochar types were amended with the soils. The study thus showed that biochar pyrolyzed at 300–450 °C could be used to reduce P sorption and increase P bioavailability especially in acid soils. The addition of biochar to neutral or alkaline soils might increase P retention possibly in the short-term, reducing P bioavailability. •Phosphorus bioavailability in soil solution is dependent on soil type, feedstock used and pyrolysis temperature.•Addition of biochar to acid soils decreases P retention at decreasing pyrolysis temperature.•Biochar amendment in neutral soil raises P sorption capacity at increasing pyrolysis temperature.•Phosphorus desorbability in biochar amended acid soils increases while in neutral soil it decreases.